KONSTRUKSI, SIFAT DAN DIMENSI HIMPUNAN CANTOR MIDDLE THIRD - Alfiana, Khoiroh; Khabibah, Siti; Utomo, Robertus Heri Soelistyo (MATEMATIKA, 2013)
This paper discussed about the construction of Cantor middle third set which is formed from unit interval . To construct the Cantor set, take a line and remove the middle third and remain two line segments. This Process is repeated infinite number of times. This process produces some interesting properties on Cantor middle third set, such as has uncountable many elements, contains no intervals, and is compact, perfect, and nowhere dense. By using Hausdorff dimension and self similar set, it discussed the dimension of Cantor middle third set which is a unique positive number